KONSEP SAKTI DALAM LAKON SAWITRI: ANALISIS PERTUNJUKAN WAYANG KI NARTOSABDO - Retno Dwi Intarti (LITERASI: Indonesian Journal of Humanities, 2012)
This article is aimed at discussing the form of wayang performance and sacred (sakti) concept on Sawitri shadow puppet play performed by Ki Nartosabdo. It employes hermeneutics and dramaturgy approaches. Based on the analysis it can be concluded that the main theme is “destiny can be changed” (kodrat bisa diwiradat). The mandate given in the story is that with sincerity, loyalty, and persistence, everything can be changed. The main character of the story is Dewi Sawitri. The wayang performance is presented with Surakarta style. The sacred (sakti) concept in Sawitri is manifested in spiritual behaviour, loyalty, her unwavering and unyielding stance in living her life. It is proved that she is able to contribute positively to her husband, parent in-law, parent, and the environment.Keywords: sacred, shadow pupet performance, Surakarta style